Elapsed time from symptom onset to coronary percutaneous revascularization in acute coronary syndromes: is there a gender difference?. (26th April 2021) - Garcia Bras, P; Portugal, G; Cardoso, I; Grazina, A; Castelo, A; Ferreira, V; Valentim Goncalves, A; Mendonca, T; Timoteo, A; Ferreira, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Timely coronary artery percutaneous revascularization improves outcomes in patients with ST-segment elevation myocardial infarction (STEMI) or high-risk non-ST-segment elevation (NSTE) acute coronary syndromes (ACS) patients. Female patients often have nonspecific symptomatology and thus may present to the emergency department later after symptom onset and, as such, be at higher risk for cardiovascular complications. The aim of this study was to compare the elapsed time from symptom onset to coronary revascularization between female and male ACS patients as well as compare ACS recurrence and cardiovascular mortality in a one-month follow-up in these groups. Methods: Retrospective evaluation of patients with ACS submitted to percutaneous revascularization in a tertiary center from 2005 to 2019. Elapsed time from symptom onset to revascularization was calculated (in hh:mm) and patients were followed up for one month for hospitalization for recurrent ACS or cardiovascular mortality. Data was compared between two groups: female patients and male patients. Results: 4039 patients were evaluated, mean age 63 ± 13 years, 28% female gender, female patients were older: 68 ± 13 vs 61 ± 12, p < 0.01, and had an inferior rate of previous ACS: 134 (3.3%) vs 439 (10.9%), p = 0.013. The diagnosis at hospital admission, stratified according to gender, was unstable angina in 198 (4.9%) patients: 61 (5.5%) vs 137 (4.7%), NSTEMI in 1050 (26%) patients: 355 (31.8%) vs 695 (23.8%) and STEMI in 2771 (68.6%) patients: 695 (62.2%) vs 2076 (71.1%). There was no significant difference regarding complications during hospitalization, including cardiogenic shock: 60 (1.5%) vs 139 (3.4%), p = 0.42, mechanical ventilation: 45 (1.1%) vs 135 (3.3%), p = 0.44 or cardiac arrest 64 (1.6%) vs 140 (3.5%), p = 0.23, although there was a significantly inferior rate of hospital mortality rate in female patients: 78 (1.9%) vs 120 (3%), p < 0.001. The elapsed time from symptom onset to revascularization was significantly superior in female patients (08:28 ± 05:56 vs 06:59 ± 05:38, p < 0.001) as well as across the types of ACS: NSTEMI (11:23 ± 06:03 vs 10:33 ± 06:06, p = 0.037) and STEMI (06:54 ± 05h15 vs 05:44 ± 04h54, p < 0.001), with the exception of unstable angina (09:03 ± 06h04 vs 7:51 ± 05h47, p = 0.187) At a 1-month follow-up, female patients had a significantly inferior rate of hospitalization for recurrent ACS: 11 (0.3%) vs 59 (1.5%), HR 0.48 (95% CI 0.25-0.92), p = 0.029 and no significant difference regarding cardiovascular mortality: 12 (0.3%) vs 36 (0.9%), HR 0.87 (95% CI 0.45-1.67), p = 0.677. Conclusion: In a tertiary hospital ACS population of predominantly STEMI patients, female patients had a significantly superior elapsed time from symptom onset to coronary revascularization, with 1 hour and 29 minutes difference (and 1 hour and 10 minutes difference in STEMI patients) comparing with male patients, and an inferior rate of recurrent ACS (0.3% vs 1.5%, HR 0.48, p = 0.029) in a one-month follow-up.